Hypothermia versus Normothermia after Out-of-Hospital Cardiac Arrest - Dankiewicz, Josef; Cronberg, Tobias; Lilja, Gisela; Jakobsen, Janus C; Levin, Helena; Ullén, Susann; Rylander, Christian; Wise, Matt P; Oddo, Mauro; Cariou, Alain; Bělohlávek, Jan; Hovdenes, Jan; et al. (The New England journal of medicine, 2021)
BACKGROUND: Targeted temperature management is recommended for patients after cardiac arrest, but the supporting evidence is of low certainty. METHODS: In an open-label trial with blinded assessment of outcomes, we randomly assigned 1900 adults with coma who had had an out-of-hospital cardiac arrest of presumed cardiac or unknown cause to undergo targeted hypothermia at 33°C, followed by controlled rewarming, or targeted normothermia with early treatment of fever (body temperature, ≥37.8°C). The primary outcome was death from any cause at 6 months. Secondary outcomes included functional outcome at 6 months as assessed with the modified Rankin scale. Prespecified subgroups were defined according to sex, age, initial cardiac rhythm, time to return of spontaneous circulation, and presence or absence of shock on admission. Prespecified adverse events were pneumonia, sepsis, bleeding, arrhythmia resulting in hemodynamic compromise, and skin complications related to the temperature management device. RESULTS: A total of 1850 patients were evaluated for the primary outcome. At 6 months, 465 of 925 patients (50%) in the hypothermia group had died, as compared with 446 of 925 (48%) in the normothermia group (relative risk with hypothermia, 1.04; 95% confidence interval [CI], 0.94 to 1.14; P = 0.37). Of the 1747 patients in whom the functional outcome was assessed, 488 of 881 (55%) in the hypothermia group had moderately severe disability or worse (modified Rankin scale score ≥4), as compared with 479 of 866 (55%) in the normothermia group (relative risk with hypothermia, 1.00; 95% CI, 0.92 to 1.09). Outcomes were consistent in the prespecified subgroups. Arrhythmia resulting in hemodynamic compromise was more common in the hypothermia group than in the normothermia group (24% vs. 17%, P<0.001). The incidence of other adverse events did not differ significantly between the two groups. CONCLUSIONS: In patients with coma after out-of-hospital cardiac arrest, targeted hypothermia did not lead to a lower incidence of death by 6 months than targeted normothermia. (Funded by the Swedish Research Council and others; TTM2 ClinicalTrials.gov number, NCT02908308.).
Keywords: senioři; terapeutická hypotermie; Body Temperature; výsledek terapie; Cardiopulmonary Resuscitation; Single-Blind Method; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; jednoduchá slepá metoda; Kaplanův-Meierův odhad; Hypothermia, Induced; kóma; tělesná teplota; kardiopulmonální resuscitace; ženské pohlaví; Humans; Coma; horečka; Out-of-Hospital Cardiac Arrest; lidé středního věku; Fever; zástava srdce mimo nemocnici; Female; Aged; Treatment Outcome; lidé; Male